Design and cryptanalysis of a new iterative structure - Jiajie Liu; Bing Sun; Chao Li (IET Information Security)
Abstract This study proposes a new iterative structure called the L‐Feistel structure, which shares similar procedures between encryption and decryption and could unify the Feistel structure and the Lai‐Massey structure. This paper evaluates the security of the L‐Feistel structure from the perspective of provable security and classical analysis, respectively. Firstly, it is proved that the 4‐round Key‐Alternating L‐Feistel cipher with independent round keys and independent round functions is secure against 2n/2 queries that is, birthday‐bound security. Then by presenting the dual structure of the L‐Feistel structure with SP‐type round functions, it is proven that a differential of the L‐Feistel structure is impossible when and only when it is a zero‐correlation linear hull of its dual structure. Finally, the paper constructs impossible differentials, zero‐correlation linear hulls and integral distinguishers of the L‐Feistel structure with SP‐type round functions which cover six and seven rounds, respectively, under different conditions.